Lipid enemas for meconium evacuation in preterm infants - a retrospective cohort study - Maximilian Gross; Christian F. Poets (BMC, 2021)
Abstract Background Enemas are used in preterm infants to promote meconium evacuation, but frequent high-volume enemas might contribute to focal intestinal perforation (FIP). To replace a regime consisting of frequent enemas of varying volume and composition, we implemented a once-daily, low-volume lipid enema (LE) regimen. We investigated its impact on meconium evacuation, enteral nutrition, and gastrointestinal complications in preterm infants. Methods We performed a single-center retrospective study comparing cohorts of preterm infants < 28 weeks gestation or < 32 weeks, but with birth weight < 10th percentile, before and after implementing LE. Outcomes were rates of FIP, necrotizing enterocolitis (NEC), and sepsis. We assessed stooling patterns, early enteral and parenteral nutrition. We used descriptive statistics for group comparisons and logistic regression to identify associations between LE and gastrointestinal complications and to adjust for group imbalances and potential confounders. Exclusion criteria were gastrointestinal malformations or pre-determined palliative care. Results Data from 399 infants were analyzed, 203 before vs. 190 after implementing LE; in the latter period, 55 protocol deviations occurred where infants received no enema, resulting in 3 groups with either variable enemas, LE or no enema use. Rates of FIP and sepsis were 11.9% vs. 6.4% vs. 0.0% and 18.4% vs. 13.5% vs. 14.0%, respectively. NEC rates were 3.0% vs. 7.8% vs. 3.5%. Adjusted for confounders, LE had no effect on FIP risk (aOR 1.1; 95%CI 0.5-2.8; p = 0.80), but was associated with an increased risk of NEC (aOR 2.9; 95%CI 1.0-8.6; p = 0.048). While fewer enemas were applied in the LE group resulting in a prolonged meconium passage, no changes in early enteral and parenteral nutrition were observed. We identified indomethacin administration and formula feeding as additional risk factors for FIP and NEC, respectively (aOR 3.5; 95%CI 1.5-8.3; p < 0.01 and aOR 3.4; 95%CI 1.2-9.3; p = 0.02). Conclusion Implementing LE had no clinically significant impact on meconium evacuation, early enteral or parenteral nutrition. FIP and sepsis rates remained unaffected. Other changes in clinical practice, like a reduced use of indomethacin, possibly affected FIP rates in our cohorts. The association between LE and NEC found here argues against further adoption of this practice. Trial registration Registered at the German Register of Clinical Trials (no. DRKS00024021 ; Feb 022021).